Green Marketing, Perceived Greenwashing, and Consumer Trust in Sustainable Batik Brands: Evidence from Indonesia - Wiwin; Agustin Windianingsih; Ratih Ayu Sekarini; Annisa Zahra Savina (Global Research Collaboration, 2026)
This study examines the relationship between green marketing, perceived greenwashing, and consumer trust in the context of sustainable batik brands in Indonesia. The study focuses on the Cirebon batik industry, where sustainability-oriented marketing is increasingly used to communicate environmental responsibility, but may also create consumer skepticism when environmental claims are perceived as exaggerated, vague, or insufViciently supported by actual practices. Using a quantitative explanatory design, data were collected from 200 consumers who had purchased, used, or evaluated Cirebon batik products. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The Vindings show that green marketing has a positive and signiVicant relationship with consumer trust (β = 0.452, p < 0.001), indicating that credible environmental marketing communication can strengthen consumer conVidence in sustainable batik brands. However, green marketing also has a positive and signiVicant relationship with perceived greenwashing (β = 0.389, p < 0.001), suggesting that sustainability claims may increase skepticism when consumers perceive them as insufViciently transparent or veriViable. Perceived greenwashing has a negative and signiVicant relationship with consumer trust (β = –0.301, p < 0.001). The mediation analysis further conVirms that perceived greenwashing partially mediates the relationship between green marketing and consumer trust through a signiVicant negative indirect effect (β = –0.117, p = 0.001). These Vindings suggest that green marketing operates as a double-edged strategy in the traditional creative industry context. The study contributes to sustainability marketing literature by providing empirical evidence from Indonesia’s batik industry and by highlighting the importance of transparency, credibility, and consistency between environmental claims and actual sustainability practices.